Electrospraying the Triblock Copolymer SEBS: The Effect of Solvent System and the Embedding of Quantum Dots. Issue 2 (14th February 2020) - Koekoekx, Robin; Zawacka, Natalia C.; Van den Mooter, Guy; Hens, Zeger; Clasen, Christian
Abstract : Front Cover : In article number 1900658, Christian Clasen and co‐workers show different morphologies of polymeric micro‐particles of an ABA triblock copolymer encoded with CdSe/CdS core‐shell quantum dots (QDs), obtained by electrospraying from varying solvents. The creation of poly(styrene‐ethylene‐butylene‐styrene) (SEBS) monodisperse spherical microparticles with a tunable morphology from flat, pancake shaped to spherical particles arises from the selectivity of the solvent for one of the distinct blocks in the polymer, the resulting alteration in the sol–gel state, and the related differences in solvent mass transfer within the electrosprayed droplets. The fluorescence characteristics of the final, QD embedded polymer particles and photodegradation stability indicate significant stability and dispersion quality improvement in the spherical particle morphology.